PENINGKATAN HASIL BELAJAR IPA DENGAN MENGGUNAKAN METODE PEMBERIAN LEMBAR TUGAS SISWA PADA MATERI EKOSISTIM SISWA KELAS VII 2 SMP NEGERI 2 DUMAI - Sajarotunnur (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This study aimed to improve student learning outcomes through the application of the student worksheet assignment method in class VII.2. The research was conducted in March and April 2016. The subjects of the study were 26 seventh-grade students of SMP Negeri 2 Dumai. The parameters measured in this study included students’ absorption, mastery learning, student activities, and teacher activities as supporting data. The research instruments consisted of instructional tools and data collection instruments. The instructional tools included a syllabus, lesson plans, and tests, while the data collection instruments consisted of student activity observation sheets and teacher activity observation sheets. The results of the study showed that students’ absorption in the first cycle reached 70%, which was categorized as moderate, and increased to 78% in the second cycle, categorized as high. Student mastery learning in the first cycle reached 88.46%, and slightly increased to 88.50% in the second cycle, indicating that students achieved mastery learning. Student activity in the first cycle obtained an average score of 80.76%, categorized as very good, and increased significantly to 97.5% in the second cycle, categorized as excellent. It can be concluded that the implementation of the student worksheet assignment method can improve student learning outcomes in ecosystem material for class VII.2 students of SMP Negeri 2 Dumai.